Fibromyalgia: Tinjauan Pustaka - Anggi Setiorini; Maula Al Farisi; Muhartono; M. Praditia Ansor (CV. Jasa Sukses Abadi, 2021)
Musculoskeletal chronic pain is characterized by pain and loss of function in the joints, tendons, ligaments, bones, and or muscles lasting for greater than equal to three months. There are several diseases caused by rheumatic disorders that have been identified, such as osteoarthritis, gout, rheumatoid arthritis, fibromyalgia. However, until now, chronic rheumatic disorders have become a world problem, namely “fibromyalgia”. Fibromyalgia is a syndrome characterized by generalized chronic musculoskeletal pain, hyperalgesia in specific points and psychosomatic symptoms, such as fatigue, sleep disturbances, anxiety, depression, cognitive dysfunction, headache, and gastrointestinal disorders. The prevalence of fibromyalgia in the world is higher in women than in men, which is between 2,4% to 6,8% with the ratio between women and men is 2:1. The etiology of fibromyalgia is idiopathic, but it is suspected that psychosocial factors play a role in the development of fibromyalgia. Currently, the diagnose of fibromyalgia can only be made by a comprehensive clinical examination according to the ACR (American College of Rheumatology) criteria. Therapy of fibromyalgia requires an optimal approach to the success of treatment. Therapies that can be done in patients with fibromyalgia include pharmacological therapy, complement therapy, cognitive behavioural therapy, psychotherapy and physical therapy.